2014
DOI: 10.2185/jrm.2887
|View full text |Cite
|
Sign up to set email alerts
|

Skipping Breakfast is Correlated with Obesity

Abstract: Objective: Despite the fact that the total energy intake of Japanese people has decreased, the percentage of obese people has increased. This suggests that the timing of meals is related to obesity. The purpose of the study was to investigate the relationship between the timing of meals and obesity, based on analyses of physical measurements, serum biochemical markers, nutrient intake, and lifestyle factors in the context of Chrononutrition.Participants and Methods: We analyzed data derived from 766 residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 12 publications
(13 reference statements)
4
64
1
10
Order By: Relevance
“…O café da manhã é considerado uma refeição principal que deve ser feita diariamente pela população gestante ou não 3,23 . De acordo com Cho et al 40 , o hábito de não consumir o café da manhã não é uma maneira efetiva de controlar o peso e há correlação entre este hábito e obesidade 41 . Ainda sobre comportamentos alimentares, de acordo com a Organização Mundial da Saúde, substituir o almoço e/ou jantar por lanches pode ocasionar problemas de saúde no futuro, pois os alimentos tradicionais dessas refeições são importantes fontes de fibras, minerais e vitaminas e acabam sendo substituídos por alimentos de alta densidade energética e com pior qualidade nutricional 42 .…”
Section: Discussionunclassified
“…O café da manhã é considerado uma refeição principal que deve ser feita diariamente pela população gestante ou não 3,23 . De acordo com Cho et al 40 , o hábito de não consumir o café da manhã não é uma maneira efetiva de controlar o peso e há correlação entre este hábito e obesidade 41 . Ainda sobre comportamentos alimentares, de acordo com a Organização Mundial da Saúde, substituir o almoço e/ou jantar por lanches pode ocasionar problemas de saúde no futuro, pois os alimentos tradicionais dessas refeições são importantes fontes de fibras, minerais e vitaminas e acabam sendo substituídos por alimentos de alta densidade energética e com pior qualidade nutricional 42 .…”
Section: Discussionunclassified
“…39 This association between breakfast skipping and higher body mass index (BMI) has been reported globally, primarily in cross-sectional studies. 33,[40][41][42][43][44][45][46][47][48][49][50][51] For example, in NHANES 1999 to 2002, young adults (n=5316; age, 20-39 years) who reported consuming ready-to-eat cereal were 31% less likely to be overweight/obese and 39% less likely to have abdominal obesity compared with breakfast skippers. 52 Additionally, a meta-analysis of 19 studies in the Asian and Pacific regions (n=19 108 participants) demonstrated a pooled odds ratio (OR) of 1.75 (95% confidence interval [CI], 1.57-195) for prevalence of overweight or obesity among the lowest compared with the highest breakfast consumption frequency.…”
mentioning
confidence: 99%
“…Previous studies reported that breakfast skippers have a higher energy intake during the day than breakfast eaters [11,18,42], and this increased energy intake may be associated with the current eating behavior changes [18,22]. Therefore, this study evidenced an association between the habit of skipping breakfast with obesity and a higher total calorie intake, which can be understood as a metabolism compensation [38,43], as the individual eats more calories during the day to compensate the lack of breakfast [9,44].…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of fasting glucose, total cholesterol, high-density lipoprotein (HDL) cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c) and triglycerides (TG) were measured by using specific enzymatic Elisa kits (DSA BioELISA, USA) [18]. The individuals were previously advised to not perform vigorous physical exercises 24 h and/or consume alcohol 72 h prior to blood collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation